Hegemoni Feminisme dalam Wacana Naratif Perempuan Berkalung Sorban Karya Abidah El Khalieqy - Lalu Mas’ud; Sri Setyawati Mulyaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to reveal the form of feminism hegemony in Women with the Turban narrative discourse by Abidah El Khalieqy. This research method uses a qualitative approach to literature or content analysis. The primary data source in this research is the novel Perempuan Berkalung Surban by Abidah El Khalieqy. The data collection technique in this study used library techniques and was analyzed using a hermeneutic model. The presentation of the analysis results is prioritized in an informal way rather than a formal one so that the description can be explained in more detail. The study results indicate that the hegemony of feminism is revealed through the conversations of the characters and expressive actions that are seen in the words and behaviors that lead to the assertiveness of the female characters. In addition, a shift in the ideology of feminism was found in the narrative discourse. In conclusion, the hegemony of feminism is revealed through the conversations and actions of the characters in the form of refuting, debating, persuading, influencing, suing, reacting and actions related to sexual activity. Keywords: Hegemony Feminism, Novel, Narrative Discourse